2012
DOI: 10.1016/j.jcis.2012.06.066
|View full text |Cite
|
Sign up to set email alerts
|

Biomimetic monolayer films of monogalactosyldiacylglycerol incorporating ubiquinone

Abstract: Ubiquinone and plastoquinone are two of the main electron and proton shuttle molecules in biological systems, and monogalactosyldiacylglycerol (MGDG) is the most abundant lipid in the thylakoid membrane of chloroplasts. Saturated MGDG, ubiquinone-10 (UQ) and MGDG:UQ mixed monolayers at the air/water interface have been studied using Surface Pressure-Area isotherms and Brewster Angle Microscopy. Moreover, the transferred Langmuir-Blodgett films have been observed by Atomic Force Microscopy. The results show tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
37
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(47 citation statements)
references
References 49 publications
10
37
0
Order By: Relevance
“…1), the AFM results reported in our previous work [31] and the electrochemical discussion presented in the previous section. The description of the UQ positons in the MGDG monolayer will be made using the model proposed by Söderhäll and Laaksonen [52].…”
Section: Global Sight Of the Mgdg:uq System Transferred On Itomentioning
confidence: 74%
See 3 more Smart Citations
“…1), the AFM results reported in our previous work [31] and the electrochemical discussion presented in the previous section. The description of the UQ positons in the MGDG monolayer will be made using the model proposed by Söderhäll and Laaksonen [52].…”
Section: Global Sight Of the Mgdg:uq System Transferred On Itomentioning
confidence: 74%
“…The AFM studies of the LB films of pure MGDG and MGDG:UQ mixtures on mica reported in [31] indicated that the MGDG and the MGDG:UQ mixtures with low UQ content, both at low surface pressure, present similar covered area by the LC state, whereas the MGDG:UQ 5:1 ratio presents a markedly lower covered area by this LC state. These observations indicate that UQ is present in both physical states (LE and LC) in the MGDG:UQ mixtures.…”
Section: Global Sight Of the Mgdg:uq System Transferred On Itomentioning
confidence: 99%
See 2 more Smart Citations
“…The Langmuir technique has been applied previously by the author to study the behaviour of lipid and phospholipid films [28,29]. In this work Langmuir films have been obtained from lipid-containing artificial tears and the corresponding surface pressure-area isotherms registered.…”
Section: Introductionmentioning
confidence: 99%